Lack of an association between anticipatory alpha oscillations and attentional selection in children with attention-deficit/hyperactivity disorder. (June 2022) - Li, Bingkun; Guo, Jialiang; Zhao, Chenguang; Luo, Xiangsheng; Kong, Yuanjun; Chen, Yanbo; Liu, Hongyu; Sun, Li; Song, Yan
Highlights: Typically developing children with higher cue-induced alpha modulation have larger target-elicited N2pc. The temporal association of "cue alpha-target N2pc" is absent in children with ADHD. Children with ADHD could not sustain hemispheric alpha lateralization. Abstract: Objective: Attention-deficit/hyperactivity disorder (ADHD) is characterized by attention problems. The current study investigated whether and how anticipatory alpha oscillations, the subsequent target-elicited N2 posterior-contralateral component (N2pc) and their relationship contributed to attention problems in children with ADHD. Methods: Electroencephalograms (EEGs) were recorded from 8−13-year-old children with ADHD and typically developing children during a cued visuospatial covert attention task. Results: Children with ADHD could not sustain hemispheric alpha lateralization during the late stage of the cued period. Similar to the pattern of adults, high-accuracy typically developing children showed a strong positive correlation between the degree of cue-induced anticipatory alpha lateralization and the subsequent target-evoked N2pc amplitude, the latter of which further predicted behavioral performance. However, only the aberrant "cue alpha-target N2pc" temporal relationship was related to symptom severity and behavioral performance in children with ADHD. Conclusions: We showed that the temporal association of "cue alpha-target N2pc" was already present in some typically developing children. However, children with ADHD might need more time to develop this temporal association. Significance: Our results provide neurophysiological evidence that the developmental origin of covert spatial attention is related to the temporal association between low-frequency brain oscillations and event-related potentials (ERPs).